Validity of pulse oximetry measures for heart rate and oxygen saturation during profound hypoxia in normobaric simulated extreme altitudes - Harald Vikne; Jon Arild Kjeserud; Willy Westgaard; Ruben Baalsrud Westlie; Jan Ivar Kåsin; Jon Ingulf Medbø; Terje Gjøvaag; Nils Henrik Holmedahl (PLoS ONE, 2025)
Introduction Commercial pulse oximeters may not be well calibrated for oxygen saturations below 70%, conditions that may be met in high altitude aviation and mountaineering. We therefore examined the bias and variability of heart rate (HR) and blood oxygen saturation (SpO2) of four different pulse oximeters (PO) at arterial blood oxygen saturation (SaO2) between 55 and 100%. Methods Seventeen healthy participants (age 33 ± 11 (mean ± standard deviation (SD)) yr) were exposed to controlled desaturation at rest by stepwise reduction of the oxygen fraction in the breathing air between 20.9 and 8%. Parallel measurements of HR (n = 383) and blood oxygen saturation (n = 304) from four pulse oximeters (RAD-97, PM100N, M7500 and Nell1-SR) and from reference instruments (by hemoximetry and electrocardiography (ECG)) were taken during the exposure. The validity was assessed in intervals of 55–70%, 70–85% and 85–100% SaO2 using the Bland-Altman method (bias and 95% limits of agreement (LoA)) and the root mean square error for variability. The demarcation criteria for agreement between methods were ±6 percentage points O2Hb saturation and ±6 bpm HR. Results At the 85–100% SaO2 interval, all POs but the Nell1-SR were in agreement with the reference for O2 saturation. Only M7500 agreed with the reference for the 70–85% interval and none of the POs were in agreement with the reference for the 55–70% interval. The pulse oximeters and ECG were not in agreement for HR at neither the 55–70% nor the 85–100% interval but agreed at the 70–85% interval except the RAD-97. All pulse oximeters increased the bias or the variability for SpO2 significantly by reductions in oxygen saturation, while no systematic differences were found for HR. Conclusion The study shows that medically approved pulse oximeters are not in agreement with reference measurements of neither blood oxygen saturation nor HR at SaO2 levels below 70%, and their readings should therefore be interpreted cautiously during severe desaturation.